Dario neela, a new species of badid fish from the Western Ghats of India (Teleostei: Percomorpha: Badidae) - Britz, Ralf; Anoop, V.k.; Dahanukar, Neelesh (Zootaxa, 2018)
Dario neela, is described from a small tributary stream of the Kabini River in northern Kerala, India. It can be distinguished from congeners by the male colouration in life, which shows wide rims of iridescent blue in all median fins and the pelvic fin. It is further distinguished from all species of Dario, except D. urops by the number of abdominal vertebrae (14 vs. 11–13), and from all Dario species except D. urops and D. huli by the presence of a conspicuous black blotch on the caudal-fin base. Dario neela is distinguished from D. urops by the absence of the horizontal suborbital stripe and presence of a series of up to eight black bars on the body; and from D. huli by 27–28 vertebrae and 27 scales in a lateral row and the absence of teeth from hypobranchial 3. Dario neela is genetically divergent from both Western Ghats congeners in the mitochondrial CO1 gene, showing an uncorrected p-distance of 5.9% with D. urops and 13.1% to D. huli.